PENGARUH LEVERAGE, PENURUNAN ARUS KAS OPERASI, FIXEDASSET INTENSITY, DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEPUTUSAN REVALUASI ASET TETAP - Haykal, Muhammad; Munira, Raudhatul (Department of Accounting, Faculty of Economics & Business, 2021)
This study aims to examine the effect of leverage, decreased operating cash flow, fixed asset intensity, and company growth on fixed asset revaluation decisions in chemical sub-sector companies listed on 5 ASEAN exchanges in 2017-2019. The data used in this research is secondary data that comes from the financial reports of each stock exchange. The number of samples in this study were 135 observations using purposive sampling technique. Data is accessed through the website www.idx.co.id, www.bursamalaysia.com, www.sgx.com, www.edge.pse.com.ph, and www.set.or.th. Methods of data analysis in this study using logistic regression analysis method. The results showed that fixed asset intensity had a positive and significant effect on fixed asset revaluation decisions, while leverage, decreased operating cash flow, and company growth had no effect on fixed asset revaluation decisions.